2022
DOI: 10.3390/antiox11081546
|View full text |Cite
|
Sign up to set email alerts
|

Stress Hormones Cortisol and Aldosterone, and Selected Markers of Oxidative Stress in Response to Long-Term Supplementation with Omega-3 Fatty Acids in Adolescent Children with Depression

Abstract: Late childhood and adolescence are crucial periods of brain development with high vulnerability to environmental insults. The aim of this study was to test the hypotheses that in adolescents with depression (a) 12 weeks-supplementation with omega-3 fatty acids results in the attenuation of salivary stress hormone concentrations; (b) the mentioned supplementation improves potentially disrupted daily rhythm of stress hormones; (c) stress hormone concentrations correlate with values of selected markers of oxidati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 33 publications
(49 reference statements)
0
9
0
Order By: Relevance
“…This work is a part of the DEPOXIN project (ISRCTN81655012). A detailed description of the study design, recruitment of patients, inclusion and exclusion criteria, interventions, and previous study results are presented in recent publications ( 7 , 15 , 21 23 ). For readers’ convenience, key information about the design of the project is given in Supplements as Supplement - Study design.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This work is a part of the DEPOXIN project (ISRCTN81655012). A detailed description of the study design, recruitment of patients, inclusion and exclusion criteria, interventions, and previous study results are presented in recent publications ( 7 , 15 , 21 23 ). For readers’ convenience, key information about the design of the project is given in Supplements as Supplement - Study design.…”
Section: Methodsmentioning
confidence: 99%
“…The samples were stored at −20°C until analyzed. Details of saliva collection are described in our paper ( 15 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The renin-angiotensin-aldosterone system (RAAS) is a critical part of the vasoactive hormone pathway, in which aldosterone plays a key role. When RAAS is stimulated and activated, angiotensin II stimulates adrenal glomerular cells to release aldosterone, which then causes a series of pathophysiological changes such as tissue inflammation ( 7 ), fibrosis ( 8 ) cell proliferation ( 9 ), oxidative stress ( 10 ) and neovascularization ( 11 13 ) ( Figure 1 ). Based on these findings, researchers confirmed that aldosterone is critical in the pathological mechanism of cardiovascular disease and chronic kidney disease ( 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Depressed children and adolescents have shown HPA axis dysregulation and higher basal cortisol levels compared to healthy controls (Silberg et al, 1999). This enhanced cortisol secretion is associated with: i) increased oxidative tissue damage in adolescent children with depression (Oravcova et al, 2022); ii) a deficit of serotoninergic system (Hughes et al, 1996) combined with a lower expression/function of the serotonin transporter than in adults and a reduced clinical response to selective serotonin reuptake inhibitors (SSRIs) (Bowman And Daws 2019).…”
Section: Introductionmentioning
confidence: 99%